2002
DOI: 10.1136/adc.86.5.356
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of long term intravenous bisphosphonate treatment of osteogenesis imperfecta

Abstract: Aim: To find an effective symptomatic treatment for osteogenesis imperfecta (OI). Methods: In a prospective observational study disodium pamidronate (APD) was given as monthly intravenous infusions to 28 children and adolescents (aged 0.6-18 years) with severe OI or a milder form of the disease, but with spinal compression fractures. Results: During treatment for 2-9 years, dual energy x ray absorptiometry measurements of the total body and of the lumbar spine showed a gradual increase in bone density. All bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
1
14

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(200 citation statements)
references
References 27 publications
10
175
1
14
Order By: Relevance
“…Attempts to use bisphosphonates as a treatment for OI were pioneered by Glorieux et al 45 An open-label trial of cyclical intravenous Pamidronate (a bisphosphonate) was reported by Glorieux et al and the effects of relatively long-term use in adults by Astrom and Soderhall 46 and Zeitlin et al 47 Falk et al 48 replicated the study of Glorieux et al in children over 22 months of age, but of note did report one child with fracture nonunion after treatment with Pamidronate. Nonunion is known to occur in individuals with OI not receiving Pamidronate and the relevance of this observation is thus not clear.…”
Section: Bisphosphonate Therapymentioning
confidence: 99%
“…Attempts to use bisphosphonates as a treatment for OI were pioneered by Glorieux et al 45 An open-label trial of cyclical intravenous Pamidronate (a bisphosphonate) was reported by Glorieux et al and the effects of relatively long-term use in adults by Astrom and Soderhall 46 and Zeitlin et al 47 Falk et al 48 replicated the study of Glorieux et al in children over 22 months of age, but of note did report one child with fracture nonunion after treatment with Pamidronate. Nonunion is known to occur in individuals with OI not receiving Pamidronate and the relevance of this observation is thus not clear.…”
Section: Bisphosphonate Therapymentioning
confidence: 99%
“…A recent study showed that bisphosphonates can prevent osteoblast and osteocyte apoptosis, which is dependent on the expression of connexin (Cx)43 [14]. In addition, a study of intravenous pamidronate therapy for OI patients showed a gradual increase of lumbar bone density and a decrease of bone turnover [10]. As a result, bisphosphonate therapy is increasingly used for OI and other osteoporotic conditions in children; however, the most effective dosing regimen has yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Gene analysis showed a novel heterozygous missense mutation of COL1A1 (c.2T>G, p.Met1Arg) in the patient and his mother, which was previously reported [9]. We treated with monthly cyclic pamidronate infusion with the following protocol: 10 mg/m 2 body surface area (BSA) for 1 ~ 3 months, 20 mg/m 2 for 4 ~ 6 months, and 30 mg/m 2 after 7 month [10]. Pamidronate was intravenously infused over 4 h at concentration of less than 0.1 mg/mL in isotonic saline.…”
Section: Casementioning
confidence: 99%
“…Intravenous pamidronate or oral alendronate improve quality of life and inhibit bone resorption thus increasing bone mineralisation 7,8 .…”
Section: Discussionmentioning
confidence: 99%